LIST OF DOCUMENTS PUBLISHED BY GOVERNMENT OF RUSSIAN FEDERATION AND DEPARTMENT OF STATE SANITARY SURVEILLANCE OF MINISTRY OF PUBLIC HEALTH OF RUSSIAN FEDERATION ON SEVERE ACUTE RESPIRATORY SYNDROME - article Editorial (Acta Biomedica Scientifica, 2020)
.